Publikasi Ilmiah Mahasiswa melalui Proyek Penulisan Akademik Kontinum pada Kebijakan Pendidikan Tinggi di Indonesia - Darmalaksana, Wahyudin; Anditasari, Putri; Fikra, Hidayatul; Fitriani, Fitriani (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to discuss the scientific publication of students through the continuum academic writing project on higher education policy in Indonesia. This study uses a qualitative approach with a field study method. The results and discussion of the study indicate that the continuum academic writing project plays an effective role because there is a continuous time allocation in leveraging student scientific publications even though it has not been accommodated in higher education policy in Indonesia. This study concludes that student scientific publications through the implementation of the continuum academic writing project will be more effective if they receive policy accommodation from higher education regulations in Indonesia. This study recommends that professionals support the continuum academic writing project in Indonesian higher education.